THE LIMIT OF RED SEAWEED (Eucheuma cottonii) SUBSTITUTION IN SNAKEHEAD FISH (Channa striata) NUGGETS BASED ON SENSORY EVALUATION - Krishna Purnawan Candra; Hendra Saputra; Arboby Gunawan; Bernatal Saragih; Hudaida Syahrumsyah; Yuliani Yuliani (AGROINTEK, 2020)
Snakehead fish (Channa striata), a freshwater fish, is known to havefunctional properties in helping the process of healing burns andwounds after surgery. Besides that, the use of seaweed as a source offood fiber is also widely reported. This research was conducted todesign fiber-rich fish nuggets. The purpose of this study was todetermine the maximum levels of seaweed substitution in theprocessing of snakehead fish nuggets based on sensory properties.Single-factor experiment (seaweed, Eucheuma cottonii, substitution)arranged in a Completely Randomized Design with four replicationswas applied in this study. The parameters observed were hedonic andhedonic quality sensory properties for the attributes of color, aroma,texture, and taste of nuggets. The data obtained were analyzed by theFriedman Test, followed by the Wilcoxon Rank Test to detect thedifferences between treatments. Treatment of up to 75% seaweedsubstitution (0, 25, 50, and 75%) decreases significantly (p 0.05) thehedonic sensory acceptance of the snakehead fish nuggets for allattributes except the texture which shows an increase. Whereas, thetreatment with substitution of seaweed in the narrow percentage of 0,5, 10, 15, and 20% gave an expected result, which showed that therewas no significant difference (p 0.05) of the hedonic sensoryresponse for the overall acceptance. Nevertheless, 15% of seaweedsubstitution provides the best hedonic sensory response for overallacceptance. These results indicate that 15% of seaweed (Eucheumacottonii) substitution is recommended for use in the processing ofsnakehead fish nuggets.